2020
DOI: 10.1128/aem.00306-20
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom-Up Approach To Develop a Synthetic Microbial Community Model: Application for Efficient Reduced-Salt Broad Bean Paste Fermentation

Abstract: Humans have used high salinity for the production of bean-based fermented foods over thousands of years. Although high salinity can inhibit the growth of harmful microbes and select functional microbiota in an open environment, it also affects fermentation efficiency of bean-based fermented foods and has a negative impact on people’s health. Therefore, it is imperative to develop novel defined starter cultures for reduced-salt fermentation in a sterile environment. Here, we explored the microbial assembly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…Atopostipes suicloacalis, Atopococcus tabaci, Oceanobacillus chironomi, Staphylococcus gallinarum, Enteractinococcus lamae, Facklamia tabacinasalis as well as Alloiococcus genera also predominantly defined the final composition of Toombak. Furthermore, Staphylococcus cohnii was found to be highly abundant amongst Toombak samples analysed by Smyth et al [ 85 ], while Staphylococcus gallinarum was the most abundant species in our samples; known to be highly salt tolerant [ 86 ].…”
Section: Discussionmentioning
confidence: 78%
“…Atopostipes suicloacalis, Atopococcus tabaci, Oceanobacillus chironomi, Staphylococcus gallinarum, Enteractinococcus lamae, Facklamia tabacinasalis as well as Alloiococcus genera also predominantly defined the final composition of Toombak. Furthermore, Staphylococcus cohnii was found to be highly abundant amongst Toombak samples analysed by Smyth et al [ 85 ], while Staphylococcus gallinarum was the most abundant species in our samples; known to be highly salt tolerant [ 86 ].…”
Section: Discussionmentioning
confidence: 78%
“…This is reasonable because coastal sediment microorganisms generally adapt to the saline environments, thus promoting the microbial α-diversity and activity (Morrissey et al, 2014). Low salinity sediments may provide appropriate mineral elements for microbial growth and promote their biodiversity (Jia et al, 2020). Furthermore, the increased relative abundances of keystone OTUs could contribute to the α-diversity of bacterial and archaeal communities.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the concentrations of tyrosine and phenylalanine were slightly decreased until the end of fermentation. In our previous researches, we found that during soybean paste fermentation, A. oryzae 3.042 dominated the early and middle fermentation process, while Bacillus , Staphylococcus , Weissella , and Zygosaccharomyces genera were found to be responsible for the late fermentation (Jia et al., 2020). Therefore, the top 12 bacteria strains ( L. acidipiscis , P. acidilacticis , T. halophilus , E. faecium , S. piscifermentans , S. carnosus X1, W. confusa , S. piscifermentans , P. lolii , P. pentosaceus , S. carnosus X2, and W. paramesenteroides ) and one fungi strain ( A. oryzae 3.042) were selected and their effect on tyrosine accumulation was tested.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure 4, the tyrosine concentration increased in the first 60 hr and significantly decreased afterward. In soybean paste fermentation, A. oryzae 3.042 was the dominant microbe in the first 20 days and it gradually disappeared in the following fermentation period (Jia et al., 2020). Since the other important microbes in soybean paste fermentation had few effect on tyrosine accumulation, we proposed that the majority of tyrosine in soybean paste were produced by the degradation of proteins through the proteolytic enzymes secreted by A. oryzae 3.042 (Zhou et al., 2019).…”
Section: Resultsmentioning
confidence: 99%